Adult safeguarding managers' understandings of self‐neglect and hoarding. (17th May 2022) - Owen, Jennifer; Woolham, John; Manthorpe, Jill; Steils, Nicole; Martineau, Stephen; Stevens, Martin; Tinelli, Michela
Abstract: Self‐neglect and hoarding are behaviours that are hard to define, measure and address. They are more prevalent among older people because of bio‐psycho‐social factors, which may be exacerbated by advancing age. This paper aims to further understandings of self‐neglect and hoarding in England's Care Act 2014 context, drawing on a study involving qualitative interviews with local authority adult safeguarding managers who play an important role in determining interventions with individuals who self‐neglect and/or hoard. Online interviews were conducted with adult safeguarding leads and managers from 31 English local authorities in 2021. Interview data were subject to thematic analysis. This paper explores the commonalities and differences in adult safeguarding managers' understandings of the causes and consequences of self‐neglect and/or hoarding among older people, which are likely to have tangible impacts on service provision in their local authority, and influencing of wider changes to policies and procedures. Most participants understood these phenomena as caused by a range of bio‐psycho‐social factors, including chronic physical conditions, bereavement, isolation. A minority took a more clinical or psycho‐medical perspective, focusing on mental ill‐health, or referred to the social construction of norms of cleanliness and tidiness. Whatever their understanding, by the time such behaviours are brought to the attention of safeguarding professionals a crisis response may be all that is offered. The implications of the findings are that other agencies should be encouraged to provide more early help to older people at risk of self‐neglect and/or of developing harmful hoarding behaviours, and that sustained engagement with those affected may help to understand some of the causes of these behaviours to enable effective support or practice interventions.